The Influence of Brand Image and Marketing Mix on General Patient Satisfaction - Alfiannor, Alfiannor (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This study aims to analyze the effect of brand image and marketing mix on general patient satisfaction at H. Abdul Aziz Marabahan Hospital. This type of research is quantitative research. The population of this study were 176 general patients and a sample of 76 general patients selected by sampling method with the slovin formula. Data collection was carried out by means of interviews using a questionnaire. The collected data were analyzed using multiple linear regression tests. Based on the results of the study, brand image has a partial effect on general patient satisfaction at H. Abdul Aziz Marabahan Hospital. Partial marketing mix has significant effect on general patient satisfaction at H. Abdul Aziz Marabahan Hospital. Brand image and marketing mix simultaneously influence general patient satisfaction at H. Abdul Aziz Marabahan Hospital